Study on Seismic Performance of Rebar Sleeve Grouting Connection in Prefabricated Concrete Buildings - Syamsunur, Deprizon; Naiyuan, Cui; Surol, Salihah; Hisyam Jusoh, Muhammad Noor; Md Noh, Nur Ilya Farhana; Ardana, Putu Doddy Heka (International Journal of Engineering, Science and Information Technology, 2025)
This research aims at assessing the reliability of rebar sleeve grouting connections used in P.C building under cyclic lateral loadings. Such connections are necessary for structural stability at the time of an earthquake. It is essential to determine their performance for improving the safety in prefabricated structures. For the research, three full scale column to foundation samples that used standardized construction materials and methods were used in testing. Rebar sleeve grouting connections were each confined and encased in high strength grout and had ribbed steel sleeves to enhance the mechanical interlocking. Specific performance factors like load transfer efficiency, deformability and energy absorption were recorded as lateral cyclic loads were progressively applied to simulate actual seismic actions. Measurements were made using load cells, displacement transducers, and strain gauges while videotaping of the experiment was done with normal and high-speed cameras. The analysis also showed that of all the factors, sleeve geometry, grout quality and bond strength means have larger impact on seismic performance. Energy dissipation and deformation capacity was captured by displaying that ductile failure modes included rebar yielding and controlled grout cracking. All these findings are relevant to understanding the learnings available for the prefabricated structure design in improving the construction practices and defining the standard tests required to enhance the Seismic performance of the structures.